The Correlation between Introvert Personality and Reading Comprehension at the Sixth Semester Students of English Language Education - FKIP UIR - Anugrah, Bulan; Idayani, Andi (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
Reading ability is crucial in English language learning in Indonesia, which is taught at the beginning and comprehension levels. There are several factors that affect reading comprehension, such as vocabulary, reading techniques, motivation and personality. Introverts prefer internal processes and deep relationships, while extroverts engage in verbal discussions to improve comprehension. This study aims to find out whether there is a correlation between introvert personality and reading comprehension at the sixth semester students of English Language Education of FKIP UIR. The method of this quantitative study utilized a correlational design to explore the correlation. Data were collected from 22 introverted students using Eysenck's Personality Inventory questionnaire and TOEFL ITP section 3 reading comprehension test trough google form. The analysis employed Pearson’s correlation to measure the correlation between these variables. The result of this study show there is no significant correlation between introverted personality and reading comprehension, with a rxy value of 0.044 < rt value of 0.444 and a tcounted value of 0.197 < ttable value of 1.72. Teachers can improve learning by recognizing whether students are more introverted or extroverted, which allows for teaching strategies tailored to individual learning styles. Understanding personality types helps create an inclusive learning environment and allows students to capitalize on their strengths.